1995
DOI: 10.1111/j.1748-720x.1995.tb01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethics Consultation: Persistent Brain Death and Religion: Must a Person Believe in Death to Die?

Abstract: We first heard about this case from nurses in one of our intensive care units (ICUs) while we were conducting an inservice. When the session was over, we discussed it between ourselves, and decided that it must have been misrepresented. The case had been presented as one of a teenager who was brain dead, had been so for six months, yet had been brought into the ICU for treatment. We have run into this before, we thought: medical professionals confusing brain death with persistent vegetative state (PVS). But, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…Respondents reported that their behavior in these situations was highly motivated by fear of litigation and media coverage, both of which have been reported to occur when families are dissatisfied. 3,7,8,16 Many respondents requested the creation of guidelines for management of situations in which families object to discontinuation of organ support after DNC. Although delaying discontinuation of organ support can give a family time to come to terms with a patient's death, 6,7,16 it can also promote confusion about the patient's status and increase the risk of complicated grief (a state of profound grief for greater than 6 months that is marked by disbelief, anger, bitterness, intrusive thoughts of the deceased, and difficulty moving on in life).…”
Section: Solo Practice 21 20mentioning
confidence: 99%
See 4 more Smart Citations
“…Respondents reported that their behavior in these situations was highly motivated by fear of litigation and media coverage, both of which have been reported to occur when families are dissatisfied. 3,7,8,16 Many respondents requested the creation of guidelines for management of situations in which families object to discontinuation of organ support after DNC. Although delaying discontinuation of organ support can give a family time to come to terms with a patient's death, 6,7,16 it can also promote confusion about the patient's status and increase the risk of complicated grief (a state of profound grief for greater than 6 months that is marked by disbelief, anger, bitterness, intrusive thoughts of the deceased, and difficulty moving on in life).…”
Section: Solo Practice 21 20mentioning
confidence: 99%
“…3,7,8,16 Many respondents requested the creation of guidelines for management of situations in which families object to discontinuation of organ support after DNC. Although delaying discontinuation of organ support can give a family time to come to terms with a patient's death, 6,7,16 it can also promote confusion about the patient's status and increase the risk of complicated grief (a state of profound grief for greater than 6 months that is marked by disbelief, anger, bitterness, intrusive thoughts of the deceased, and difficulty moving on in life). 3,5,6,8,17 For clinicians and hospital personnel, ongoing treatment after DNC can be seen as a violation of a patient's dignity and bodily integrity, and a misallocation of valuable resources including an intensive care unit bed, medical equipment, medications, and health care professionals' time and energy.…”
Section: Solo Practice 21 20mentioning
confidence: 99%
See 3 more Smart Citations